The unpaid care work during the pandemic in Costa Rica - Sandoval-Carvajal, Irma (2023)
The purpose of this article is to analyze the impact on unpaid care work in Costa Rica due to the COVID-19 pandemic. To achieve this, data from the National Household Survey of 2020 and 2021, years of lockdown, are used and compared with 2019. Three indicators were employed: weighted rates that take into account both participation, the average time spent on unpaid care work, and per capita time for women (or men) at the household level. The results show that, during the lockdown, gender patterns remained unchanged; women continued to take on unpaid care work within households, and consequently, gender gaps persisted, and in some cases, even increased for certain age groups. While not altering these gender patterns, there were increases in men's participation, especially in 2020 compared to 2019. Meanwhile, women also increased their participation, particularly among those aged 15 to 60.